Coolest Student Papers at Finland Futures Research Centre 2022-2023 - Tulevaisuuden tutkimuskeskuksen valittuja opiskelijatöitä 2022–2023 - Heino Hanna; Ahlqvist Toni; Ahvenharju Sanna; Ferreira-Aulu Marianna; Kaboli Akhgar; Lehtiö Kati; Puustinen Sari; Pöllänen Markus; Shaw Morgan; Siivonen Katriina; Taylor Amos; Arvonen Anne (Turun yliopisto, 2025)
We are proud to present a selection of our finest student papers from the academic year 2022–2023. The Coolest Student Papers publication has already been published since 2016 and it has shown our students’ capability to academic working and writing. The aim of this publication is both to give an example of a good student work to others and provide a publication forum for the students.
This issue covers courses from different study programs that are all coordinated by the Finland Futures Research Centre. It includes the international Master’s Degree Programme in Futures Studies, the interdisciplinary team work course of Sustainable Development Studies and courses organised by Finland Futures Academy (taught in Finnish). Each course forms its own section with a description of intended learning out-comes, an introduction by the teacher(s), followed by the papers.
The topics range from health data ownership and healthcare scenarios to Disaggregative Delphi Approach and from method comparison to the frameworks of social sustainability and forest utilisation. All the selected papers present good quality academic thinking and writing.
I wish you get inspired while reading!